THE EFFECT OF INFLUENCER MARKETING, CONTENT MARKETING, AND PRICE PERCEPTIONS ON CONSUMER PURCHASE INTENTION (AN INVESTIGATION OF LUXCRIME COSMETIC CONSUMERS IN KARAWANG) - Hermawan, Hendra; Hersona, Sonny; Suyaman, Dede Jajang (Islamic University of Kalimantan MAB Banjarmasin, 2024)
This research aims to evaluate the impact of Influencer Marketing, Content Marketing, and Price Perception on Purchase Intention in Luxcrime Cosmetics products in Karawang. The research method applied is quantitative with hypothesis testing. A total of 100 respondents who used Luxcrime Cosmetics products in Karawang were the research samples.Data analysis was carried out using multiple linear regression, coefficient of determination (R2), partial correlation coefficient, t test, F test, and classical assumption test with the help of SPSS version 20 statistical software. Questionnaires were the main source of data in this research. Research findings show that Influencer Marketing has a significant influence on purchasing intention in Luxcrime Cosmetics products in Karawang. Meanwhile, Content Marketing also has a significant influence on intention in purchasing these products. On the other hand, Price Perception does not show a significant influence on purchase intention in Luxcrime Cosmetics in Karawang. Simultaneously, Influencer Marketing, Content Marketing, and Price Perception together influence intention in purchasing the product.